Discourse of Ecological Damage as a State Financial Loss: Evidence from Indonesia - Hartanto, Ponco; Wijaya, Subagio Gigih; Chancy, Riamy (Journal of Law, Environmental and Justice, 2024)
This study examines the prevailing focal point in Indonesia's public discourse, recognizing that corruption offenses significantly influence economic conditions and social dynamics. Notably, in the context of combating corruption in Indonesia, there exists a discourse that acknowledges ecological and environmental losses as forms of state financial losses. This perspective consequently paves the way for categorizing every environmental crime as a potential corruption offense. This study employs a normative legal framework, utilizing case law, statutory analysis, and conceptual methodologies. The research findings indicate that framing ecological loss as a financial detriment to the state is plausible. In instances of corruption leading to environmental degradation and the depletion of natural resources, the assessment of environmental damage must be integrated into the broader context of state losses or the state's overall economy. Ultimately, it is inevitable that the government will be responsible for all expenses associated with reinstating the function and significance of the environment as a matter of public interest that requires preservation